2010
DOI: 10.1097/mao.0b013e3181cc0607
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index as a Risk Factor for Skin Overgrowth With the Bone-Anchored Hearing Aid

Abstract: Our study demonstrates that after Bone-Anchored Hearing Aid surgery, most patients (78/88, 88.6%) had no soft tissue reaction or had only a mild reaction that was easily treated. However, there are a definite percentage of patients who may develop significant scarring over time. This study identified a significant relationship between obesity (BMI > 30 lb/in) and extensive soft tissue reaction around the implant site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
3
10
3
Order By: Relevance
“…They found 10/88 patients (11.4%) required soft tissue revision or replacement with a longer abutment. Of the 10 patients, 9 were obese with a BMI > 30 lb/ in 2 [15]. Our study did not reach statistical significance but a trend was evident.…”
Section: Discussioncontrasting
confidence: 70%
“…They found 10/88 patients (11.4%) required soft tissue revision or replacement with a longer abutment. Of the 10 patients, 9 were obese with a BMI > 30 lb/ in 2 [15]. Our study did not reach statistical significance but a trend was evident.…”
Section: Discussioncontrasting
confidence: 70%
“…However, other risk factors previously described could not be confirmed. As stated in the introduction, Berenholtz et al (8), Rebol (9), and Kraai et al (10) identified high BMI as a risk factor for soft tissue problems, explained by the relation between body mass index and retroauricular subcutaneous tissue thickness (30). Such a significant relation between BMI and soft tissue reactions could not be identified in this series; only a trend towards higher incidence was noticed in our series.…”
Section: Comparison With Other Studiescontrasting
confidence: 49%
“…The majority of patients in our series were male, a characteristic also described by Monksfield et al 7 Another recent study identified obesity and male gender as risk factors for soft tissue overgrowth in their population of 10 BAHA patients. 10 One plausible explanation is that such patients possess comparatively thicker scalps compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Similar to our report, these studies also found that use of the longer 8.5 mm abutment reduced the need for additional surgical procedures in most patients. 7,10 Complications specifically associated with use of the longer abutment have not been described in the literature. Although a longer abutment may theoretically increase the torque applied by the processor onto the osseointegrated implant, the commercially available 8.5 mm abutment has been tested and approved by the US Food and Drug Administration, and thus far the incidence of implant loss has not increased.…”
Section: Discussionmentioning
confidence: 99%